2015
DOI: 10.1007/s12032-015-0609-8
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-conjugating enzyme E2C regulates apoptosis-dependent tumor progression of non-small cell lung cancer via ERK pathway

Abstract: The oncogenic role of ubiquitin-conjugating enzyme E2C (UBE2C) had been identified in some types of human tumors, while the clinical and biological role of UBE2C in non-small cell lung cancer (NSCLC) is still elusive. Here, we have determined the specific role of UBE2C in NSCLC. Western blot and qRT-PCR were used for detecting the mRNA level and protein level of UBE2C in NSCLC samples and cell lines, respectively. Lentivirus product was used to conduct loss of function assay. qRT-PCR array was employed to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 22 publications
0
31
0
1
Order By: Relevance
“…Ubiquitin-conjugating enzyme E2C ( UBE2C ), which encodes a member of the E2 ubiquitin-conjugating enzyme family, had been reported to serve momentous roles in various malignancies, including breast cancer, colorectal cancer, and hepatocellular carcinoma ( Ieta et al, 2007 ; Loussouarn et al, 2009 ; Chen et al, 2010 ; Bavi et al, 2011 ). For lung cancer, a study showed that progression-free survival and poorer OS of NSCLC patients was associated with UBE2C overexpression ( Kadara et al, 2009 ; Zhang et al, 2015 ). Kinesin family member 20A ( KIF20A ) belongs to the kinesin superfamily-6, a microtubule-correlated motor protein, is required for cell cycle mitosis ( Yan et al, 2012 ; Zhang et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitin-conjugating enzyme E2C ( UBE2C ), which encodes a member of the E2 ubiquitin-conjugating enzyme family, had been reported to serve momentous roles in various malignancies, including breast cancer, colorectal cancer, and hepatocellular carcinoma ( Ieta et al, 2007 ; Loussouarn et al, 2009 ; Chen et al, 2010 ; Bavi et al, 2011 ). For lung cancer, a study showed that progression-free survival and poorer OS of NSCLC patients was associated with UBE2C overexpression ( Kadara et al, 2009 ; Zhang et al, 2015 ). Kinesin family member 20A ( KIF20A ) belongs to the kinesin superfamily-6, a microtubule-correlated motor protein, is required for cell cycle mitosis ( Yan et al, 2012 ; Zhang et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitin-conjugating enzyme E2 C ( UBE2C ), a member of the E2 ubiquitin-conjugating enzyme family, was required for the destruction of mitotic cyclins and for cell cycle progression and may be involved in cancer progression. It was reported to be a promising biomarker in tumor progression and prognosis [29] , [30] , [31] , [32] .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, E2 ubiquitin conjugating enzyme UBE2C was reported to be overexpressed in multiple human tumors and might be served as a potential cancer biomarker [ 17 , 18 ]. In NSCLC, overexpression of UBE2C in tumor tissues was correlated with advanced tumor stage and apoptosis dependent cell proliferation [ 19 ]. Another study in breast cancer indicated that UBE2C down-regulation promoted the chemosensitivity of epirubicin and docetaxel resistant breast cancer cells [ 20 ].…”
Section: Discussionmentioning
confidence: 99%